2018
DOI: 10.1128/jcm.00887-18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Heterogeneous Variable-Number Tandem-Repeat Clusters Comprising Drug-Susceptible and/or Variable Resistant Mycobacterium tuberculosis Complex Isolates in the Netherlands from 2004 to 2016

Abstract: The variable-number tandem-repeat (VNTR) typing method is used to study tuberculosis (TB) transmission. Clustering of isolates with identical VNTR patterns is assumed to reflect recent transmission. Hence, clusters are thought to be homogeneous regarding antibiotic resistance. In practice, however, heterogeneous clusters are also identified. This study investigates the prevalence and characteristics of heterogeneous VNTR clusters and assesses whether isolates in these clusters remain clustered when subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…For example, although most VNTR types tended to cluster into only one sub-group in the Otago branch, type VNTR27 isolates cluster in several different groups (see the phylogenetic tree in Figure 3b ). This clustering of unrelated types has been described in other comparisons of WGS to VNTR typing ( 23 , 46 , 47 ). There were also several instances where types tended to switch back and forth within a subgroup, (see REA types 11 and 12 and REA types 1 and 6 in the tree in Supplementary Figure 5 ), as was observed by Trewby et al ( 18 ).…”
Section: Discussionsupporting
confidence: 75%
“…For example, although most VNTR types tended to cluster into only one sub-group in the Otago branch, type VNTR27 isolates cluster in several different groups (see the phylogenetic tree in Figure 3b ). This clustering of unrelated types has been described in other comparisons of WGS to VNTR typing ( 23 , 46 , 47 ). There were also several instances where types tended to switch back and forth within a subgroup, (see REA types 11 and 12 and REA types 1 and 6 in the tree in Supplementary Figure 5 ), as was observed by Trewby et al ( 18 ).…”
Section: Discussionsupporting
confidence: 75%
“…Third, transmission within ethnic groups in the new country of residence can also contribute to the higher TB rates found in asylum seekers. Occasional outbreaks have been reported in ethnic groups, including recently arrived asylum seekers (18). Finally, the WHO figures could be an underestimation of actual TB rates (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…[20] It is lower than that found in Germany, Finland and the Netherlands, all countries with low TB incidence and effective control programs. [2123]…”
Section: Discussionmentioning
confidence: 99%
“…[20] It is lower than that found in Germany, Finland and the Netherlands, all countries with low TB incidence and effective control programs. [21][22][23] Rapid identification of the most discriminative loci saves time and resources during monitoring of isolates with particular characteristics, in field investigation of past or potential outbreaks, and tracking imported isolates. In comparison with a review and analysis study of 56 articles, published between 2002 and 2019, that evaluated the discriminatory power of each locus, it is observed that five of the six highly discriminative loci found in these studies correspond to those of this research.…”
Section: Discussionmentioning
confidence: 99%